An Implicit Religious Reflex to Mechanism and a Holistic Alternative: Social Theory as a Case in Point - Hanson, Barbara Gail (Implicit religion, 2015)
This article looks at how medieval Christian politics and modes of thought have led to a an implicitly religious reflex toward mechanism in social theory. Social theoretical activity of the past 75 years has criticized conceptions of modernity, science, objectivity, and reason as artifacts of European or western thought from the 1500s onwards. Such critiques can be supplemented by looking at the way these ideas grew out of dominant monotheistic Christianity in the Middle Ages (400s-1400s) in territories that later became Europe. They were carried, via religious scholasticism, into the formation and maintenance of academia. This mechanistic reflex persists and might be transformed by alternative holistic epistemology.